SCIENTIFIC AND METHODOLOGICAL PRINCIPLES OF FORMING HIGH SCHOOL STUDENTS’ ENVIRONMENTAL COMPETENCE IN CONDITIONS OF OVERCOMING ENVIRONMENTAL CONSEQUENCES OF THE WAR - Tolochko, Svitlana (Theoretical and Methodical Problems of Children and Youth Education, 2023)
The article substantiates modern aspects of formation of high school students‘ environmental competence in the context of overcoming environmental consequences of the war, characterizes the definitions of the concepts “students’ environmental competence”, “formation of environmental competence of applicants of education”, “formation of high school students’ environmental competence in the context of overcoming environmental consequences of the war”, “educational project”, and “project-research activity”. The goal is to substantiate scientific and methodological foundations of formation of high school students’ environmental competence in conditions of overcoming environmental consequences of the war by means of project-research activities. The tasks of the research are defined as follows: to analyze the state of development of the problem of formation of high school students’ environmental competence by means of project-research activities; to clarify the essence and structure of the concepts “high school students’ environmental competence”, and “project-research activity”; to reveal the peculiarities of the system and models of formation of high school students’ environmental competence by means of project-research activities. The following methods were used to achieve the set goal and defined tasks: theoretical: theoretical analysis and generalization of literary sources; comparison, classification, generalization; deductive, inductive; system, formalization; idealization and pedagogical modelling; empirical: pedagogical observation, generalization of pedagogical experience. The importance of formation of high school students’ environmental competence in the context of overcoming environmental consequences of the war is emphasized in order to form the ability to quickly determine the level of environmental pollution and identify environmental threats during military operations, modelling the area of level of pollution spread, making an action plan to prevent the occurrence of pollution and restore territories, injured during the war. The approaches and principles are defined. The pedagogical conditions are singled out, The ways of forming high school students’ environmental competence in the context of overcoming environmental consequences of the war are outlined. A system model has been developed with implementation of innovative content, forms, methods and means of forming high school students’ environmental competence in the context of overcoming environmental consequences of the war through representation of three components: conceptual-target, content-activity and control-diagnostic.